Nutritional characteristics of maize cultivated with vermicompost - Oliva-Llaven, María Ángela; Palacios-Pola, Gabriela; Abud-Archila, Miguel; Hernández-Solis, José Alexander; Ruíz-Valdiviezo, Víctor Manuel; Gutierrez-Miceli, Federico Antonio (REVISTA TERRA LATINOAMERICANA, 2019)
This work was conducted with the objective to evaluate the effect of vermicompost application on chemical characteristics, energetic parameters and amino acids prof ile of hybrid race corn grain cultivated under open-f ield and rained conditions. The experiment was accomplished under a randomized complete design with three repetitions. Three treatments were evaluated: 1) Maize after inoculation with a commercial mycorrhizal arbuscular fungi mixture (Tec Myc 60®) plus vermicompost (V+M); vermicompost (V) and chemical fertilization (CF). Starch content in grain was 1.9% higher in V+M treatment in comparison with chemical, whereas crude protein, ether extract, crude f iber, acid detergent f iber, neutral detergent f iber, total phosphorous and phytic phosphorous were not different between treatments. Energetic parameters were not different between three treatments. 17 amino acids were evaluated of wich only tryptophan, leucine, valine, histidine and aspartic acid were higher in CF and V treatments in comparison with V+M treatment. In conclusion, it is possible to cultivate maize using vermicompost as fertilizer because chemical characteristics, energetic parameters and amino acids prof ile in maize grain were not affected compared with the maize cultivated with vermicompost added with biofertilizers (V+M) or with corn cultivated with chemical fertilizers (CF).